MENINGKATKAN HASIL BELAJAR SISWA MELALUI PENERAPAN MODEL PEMBELAJARAN PICTURE AND PICTURE PADA MATERI INTERKASI SOSIAL DI KELAS VII A SMP NEGERI 5 MUARO JAMBI TAHUN PELAJARAN 2022/2023 - Zurwati Zurwati (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2022)
This research aims to improve students learning outcomes on social interaction materials, including social interaction requirements and forms of social interaction using picture and picture learning models in class VII A of SMP Negeri 5 Muaro Jambi for the 2022/2023 academic year. This research was conducted from August to October 2022. This research consists of two cycles: planning, action, observation, and reflection. The instrument used in this study resulted from a learning test that was analyzed using a picture and picture model. The results obtained in this study are the results of tests carried out at the end of the learning process in each cycle. From the test results, an increase in learning outcomes was obtained. It was seen that there was an increase in the percentage of achievement in each cycle, namely the first cycle of the percentage of student score ranges as follows: the range of values in the category needs guidance 55.5%, the Sufficient category 7.4%, the Good category 22.2%, the very good category 14.5%. In the second cycle, there was an increase: need 0% guidance, sufficient category 7.4%, Good category 37%, very good category 55.5%.